(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2026)
This study aims to investigate the impact of monetary and fiscal policies on financial performance in Iraqi oil companies over the period 2018-2023. The study used quantitative method, by quantifying how the policy interest rate, reserve requirement ratio, and broad money growth (ΔM2) affect profitability, liquidity, and leverage of Iraqi oil firms during 2018Q1–2023Q2, the results provide actionable evidence for both policymakers and corporate decision-makers. For the Central Bank of Iraq, the estimates help calibrate tightening or easing in a way that supports financial stability without imposing unintended stress on a sector critical to national revenues. For oil-firm managers, the findings offer an empirical basis for planning capital structure, liquidity buffers, and borrowing timing under different monetary conditions and oil-price environments. Finally, by explicitly testing whether transmission changed during the COVID-19 period, the study informs crisis-ready policy design by highlighting when monetary tools become more or less effective under heightened uncertainty. This study examined the status pre and post COVID-19, so that the period was continued after the crisis has gone. Nevertheless, since the present study is aimed at providing evidence of the firm-level effects of monetary policy instruments in isolation, fiscal policy is treated as an element of the macroeconomic environment rather than as a direct explanatory variable. For that, the study recommends to investigate the effects of fiscal policy, due to the insufficient statistical data that the researcher couldn’t reach to do so.